2021
DOI: 10.1016/j.eucr.2020.101497
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis in the Canal of Nuck presenting with suprapubic pain: A case report and literature review

Abstract: The endometriosis in the Canal of Nuck is a rare condition. Most patients exhibited groin swelling but this case present with a rare condition which is suprapubic pain for 2 years. This case is a 34-year-old healthy woman had developed chronic intermittent right suprapubic pain for 2 years. Physical examination revealed a 2-cm. Reducible mass at right suprapubic area. MRI was performed and the result showed a 2.7 × 1.3 × 4.9 cm-size multiloculated cystic mass located near the round ligament of the uterus which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Additionally, a patent canal of Nuck is a rare but potential location for seeding of endometrial tissue, with a prevalence of 0.3–0.6% of all endometriosis cases [ 7 ]. Theories for extra-pelvic endometriosis include retrograde menstruation, hematogenous or lymphatic spread or coelomic metaplasia [ 7 , 8 ]. A female groin mass implicated with endometriosis is more likely to present with cyclical pain consistent with menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a patent canal of Nuck is a rare but potential location for seeding of endometrial tissue, with a prevalence of 0.3–0.6% of all endometriosis cases [ 7 ]. Theories for extra-pelvic endometriosis include retrograde menstruation, hematogenous or lymphatic spread or coelomic metaplasia [ 7 , 8 ]. A female groin mass implicated with endometriosis is more likely to present with cyclical pain consistent with menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the inferior epigastric artery may interfere with the surgical field of vision [16,17], it is necessary to adjust the surgical trocar or open the posterior wall of the inguinal canal [6]. In addition, it has been reported that HCN may be associated with endometriosis [3,18] or benign tumors and malignancy [9,19,20]. Therefore, ensuring the complete resection of HCN is particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ensuring the complete resection of HCN is particularly important. If laparoscopic resection is difficult, the courage to convert to the traditional anterior approach is required [18,21] (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%